Braincase With Natural Endocast of a Juvenile Rhinocerotinae From the Late Middle Pleistocene Site of Melpignano (Apulia, Southern Italy) - Iurino, Dawid A.; Conti, Jacopo; Mecozzi, Beniamino; Sardella, Raffaele (Frontiers in Earth Science, 2020)
Cranial remains of juvenile rhinos are exceptionally rare in the fossil record and very few is known about the ontogenetic development of their inner anatomy. In this study, we reported the first CT based description of a juvenile braincase and its natural brain endocast of a late Middle Pleistocene Rhinocerotidae from Melpignano (Apulia, Italy). The specimen belongs to an individual of about 12-18 months old, representing to date the youngest Pleistocene rhinoceros of Mediterranean Europe documented by neurocranial material. Through digital visualization methods the neurocranium has been restored and the anatomy of both, the brain and the paranasal sinuses, have been obtained and compared with those of juvenile and adult Pleistocene rhinos. We evidenced a different morphological development of the inner cranial anatomy in fossil and extant African species, especially the paranasal sinuses showed a high ontogenetic and interspecific variability among the considered sample.